Berberine as a Potential Multi-Target Agent for Metabolic Diseases: A Review of Investigations for Berberine - Wang, Shengju; Xu, Zhang; Cai, Baochao; Chen, Qiu (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Berberine (BBR) is a botanic alkaloid extracted from Coptis chinensis (Huanglian), which has various properties, compassing anti-hyperglycemia, anti-obesity, anti-inflammation, and improves insulin resistance, etc. Several researches have confirmed that BBR has effective actions in treating glycolipid metabolic abnormalities. BBR is also beneficial in regulating intestinal flora. Metabolic diseases are strongly associated with metabolic disorders, which are growing in the population and dramatically impacting human health, which also have been considered as a leading cause of diseases and death globally. This review is to evaluate the metabolic properties of BBR, and its potential application to the treatment of metabolic diseases by its effective actions on metabolic disorders.
Keywords: metabolic disorders